416 Low Allele Frequency Somatic Variants in Sporadic Saccular "Berry" Cerebral Aneurysms. (1st April 2022) - McAvoy, Malia; Karasozen, Yigit; Parada, Carolina; Busald, Tina; Osbun, Joshua W.; Ruzevick, Jacob J.; Emerson, Samuel; Nistal, Dominic A.; Tyrtova, Evgeniya; Eaton, Jessica C.; Swaminathan, Shreya; Levitt, Michael R.; et al.
Abstract : INTRODUCTION: The pathogenesis of intracranial aneurysms (IAs) is complex, with both genetic and environmental risk factors. Much effort has been devoted to identifying the molecular mechanisms of IAs to develop new therapies halting the progression of IAs. METHODS: Deep whole exome sequencing was performed for 11 anterior circulation, sporadic saccular IAs from 10 unrelated patients. Paired aneurysm-peripheral blood DNA samples were compared to evaluate the somatic saccular aneurysm exome alterations. Variants were validated with deep next generation sequencing methods. The genetic landscape of a validation cohort of 60 aneurysms was analyzed by targeted deep sequencing of a vascular panel of genes. RESULTS: Whole exome sequencing revealed somatic variants in 7 of 11 saccular aneurysms. Most coding somatic variants found were missense (68%). Somatic variants in multiple genes were common, all falling into similar allele frequencies (3-18%). Two aneurysms from one patient underwent exome sequencing with differing alterations (Acom with no alterations and MCA with 20 variants with about 8% allele frequencies). Targeted sequencing validation of these in a larger cohort revealed alterations in similar allele fractions. Saccular aneurysms harbored variants in genes falling into several functional categories including angiogenesis (PKD1), DNA repair (SFB3, DCC, MLH1), ECM (COL4A5, MMP8) and cancer genes (ERBb4 and PTCH1). Double variants, predicted to be protein/function altering were found in the following genes: DCC, ATXN1L, CCDC178, GAD2, IARS2, ERBb4, COL4A5, FAM122C, ANK2, SF3B3, ADCY7, ABCB4 and RAB11FIP1. CONCLUSION: Anterior circulation saccular IAs harbor somatic low allele fraction variants in coding genes predicted to alter protein function. Allele fractions occurred in a similar range within and between samples suggesting a cell-based population driving the pathogenesis of saccular IAs. Recurrent variants in genes known to be involved in IAs (PKD1 and COL4A5) and novel genes (ERBb4 and FAM122C) are new frontiers for further research.